ANALYSIS ON TERMS OF TRADE OF INDONESIA’S NICKEL - Harta Haryadi; Bambang Yunianto (Indonesian Mining Journal, 2016)
The import-export trade of nickel Indonesia until 2013 was always in a less prestigous position. It is due to the entire production of nickel is exported in raw materials, while nickel is continued to be imported to meet the industrial needs of stainless steel, nickel alloys, batteries and nickel metal alloys in the country. This study aims to analyze the advantages and disadvantages of export and import of nickel with a terms of trade analysis in net barter, which measures the ratio of the nickel export price with imports price, and gross barter measures the ratio of the nickel export volume to the import volume. Net barter of the analysis results shows that in 2007, the nickel export price was only 0.0121 times than the nickel import price, while gross barter indicates that the export volume was 11044.87 times compared to the import volume. Volume and value of the exports are in nickel ore), while imports in nickel oxide sinters, product of nickel metallurgy, nickel alloys, nickel waste and scrap and nickel powders and flakes. The analysis overview of nickel gives an indication that international trade (export-import) of nickel has not provided an optimal impact on the national and regional economy.